Front Cover Picture: Alkynyl−B(dan)s in Various Palladium‐Catalyzed Carbon−Carbon Bond‐Forming Reactions Leading to Internal Alkynes, 1, 4‐Enynes, Ynones, and Multiply Substituted Alkenes (Adv. Synth. Catal. 8/2019). Issue 8 (12th March 2019) - Tani, Tomohiro; Sawatsugawa, Yuuki; Sano, Yusuke; Hirataka, Yo; Takahashi, Naomi; Hashimoto, Sadahiro; Sugiura, Tetsuya; Tsuchimoto, Teruhisa
Abstract : The front cover picture, provided by Teruhisa Tsuchimoto and co‐workers, illustrates the usefulness of alkynyl–B(dan)s in palladium catalysis. The Tsuchimoto team demonstrates for the first time that the carbon–B(dan) bond can be directly used for the coupling with aryl(alkenyl) halides and allylic carbonates under palladium catalysis, and with acyl chlorides under palladium–copper catalysis. Moreover, the alkynyl–B(dan) worked well as a platform for synthesizing a structurally well‐defined tetraarylalkene through a triborylalkene. Details of this work can be found in the full paper on pages 1815–1834 (T. Tani, Y. Sawatsugawa, Y. Sano, Y. Hirataka, N. Takahashi, S. Hashimoto, T. Sugiura, T. Tsuchimoto, Adv. Synth. Catal . 2019, 361, 1815–1834; DOI: 10.1002/adsc.201801527 ).